2020
DOI: 10.1177/1747493020941658
|View full text |Cite
|
Sign up to set email alerts
|

Closure of the patent foramen ovale in patients with embolic stroke of undetermined source: A clinical expert opinion and consensus statement for the Asian-Pacific region

Abstract: Recently published long-term data from randomized controlled trials have provided evidence for the prevention of recurrent embolic stroke of undetermined source by percutaneous closure of the patent foramen ovale. However, most data were obtained from Caucasian populations and evidence on patent foramen ovale closure in Asian-Pacific patients is limited. The relative paucity in clinical data from this population, as well as the fact that Asian-Pacific patients may have higher bleeding risks than Caucasians, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The CLOSE ( 14 ), REDUCE ( 15 ) and RESPECT ( 16 ) studies about the closure of PFO with occluders were published on the New England Journal of Medicine journal in 2017, which proved that PFO occlusion could reduce the incidence of recurrent stroke more than drug therapy alone on certain conditions. Since then, many authoritative studies have been published, and guidelines in Europe ( 12 ), the United States ( 17 ), and even Asia Pacific ( 18 ) have been updated to support the use of PFO closure in the appropriate population. Therefore, our study is no longer focusing on the meaning and appropriate people of PFO closure, but discussing the safety and feasibility of a new guidance method with no angiographic guidance.…”
Section: Discussionmentioning
confidence: 99%
“…The CLOSE ( 14 ), REDUCE ( 15 ) and RESPECT ( 16 ) studies about the closure of PFO with occluders were published on the New England Journal of Medicine journal in 2017, which proved that PFO occlusion could reduce the incidence of recurrent stroke more than drug therapy alone on certain conditions. Since then, many authoritative studies have been published, and guidelines in Europe ( 12 ), the United States ( 17 ), and even Asia Pacific ( 18 ) have been updated to support the use of PFO closure in the appropriate population. Therefore, our study is no longer focusing on the meaning and appropriate people of PFO closure, but discussing the safety and feasibility of a new guidance method with no angiographic guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a clinical expert opinion and consensus statement for the Asian-Pacific region were published (11). The statement suggests that Asians should comply with international guidelines on the indication for PFO closure, similar to European guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Grade 3 (25 or more) and Grade 4 (visualization of the entire heart chamber) strongly suggest the presence of a PFO (Fig. 1) [5]. When the presence of a PFO is suspected following a contrast echo study, morphological evaluation by transesophageal echocardiography, that is, PFO height, tunnel length, and atrial septal aneurysm are evaluated [20].…”
Section: Diagnostic Process Of Pfomentioning
confidence: 99%
“…Three prospective controlled studies published in 2017 demonstrated that transcatheter closure of PFO significantly reduced the risk of recurrent paradoxical cerebral embolism compared with conventional antithrombotic therapy alone [2][3][4]. In Japan, transcatheter PFO closure has been approved as health insurance medical treatment since December 2019, and this procedure is gaining attention as a new therapeutic option for stroke prevention in young adults [5]. In 2020, the American Academy of Neurology reviewed previous criteria and stated that PFO closure probably reduces recurrent stroke risk in select patients, especially in patients younger than 60 years with a PFO and embolic-appearing infarct and where no other mechanism of stroke was identified.…”
Section: Introductionmentioning
confidence: 99%